2022
DOI: 10.1038/s41598-022-22400-z
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial biogenesis, telomere length and cellular senescence in Parkinson’s disease and Lewy body dementia

Abstract: Progressive age is the single major risk factor for neurodegenerative diseases. Cellular aging markers during Parkinson’s disease (PD) have been implicated in previous studies, however the majority of studies have investigated the association of individual cellular aging hallmarks with PD but not jointly. Here, we have studied the association of PD with three aging hallmarks (telomere attrition, mitochondrial dysfunction, and cellular senescence) in blood and the brain tissue. Our results show that PD patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 52 publications
0
17
0
Order By: Relevance
“…Telomere elongation has also been associated with schizophrenia (Nieratschker et al, 2013;Zhang et al, 2018), a disorder that genetically overlaps with ALS (McLaughlin et al, 2017). Additionally, longer telomeres are also reported in Parkinson's disease and Lewy body dementia blood and brain (Asghar et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Telomere elongation has also been associated with schizophrenia (Nieratschker et al, 2013;Zhang et al, 2018), a disorder that genetically overlaps with ALS (McLaughlin et al, 2017). Additionally, longer telomeres are also reported in Parkinson's disease and Lewy body dementia blood and brain (Asghar et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Telomere length was shorter in patients with Parkinson’s disease, Parkinson’s disease dementia, and dementia with Lewy bodies compared to controls. There is also a correlation between the number of mitochondria in the blood and risk of PD ( Asghar et al, 2022 ).…”
Section: Senescence In Neurodegenerative Diseasesmentioning
confidence: 99%
“…In fact, several pieces of evidence showed that deregulation of the proteolytic system contributed to the development of both forms of PD [ 68 , 69 ]. Effectively, a hallmark of PD is the presence of aggregated α-synuclein, ubiquitin, neurofilaments, and molecular chaperones, present as an intraneuronal inclusions called Lewy Bodies (LBs), showing that aberrant protein homeostasis results in toxic accumulation of intracellular proteins, leading to neuronal loss [ 70 , 71 ]. In healthy conditions, wild-type α-synuclein is available in its native conformation as soluble monomers, which mediates α-synuclein physiological function in presynaptic terminals [ 72 ].…”
Section: Neuronal and Muscular Alterations Found In Parkinson’s Diseasementioning
confidence: 99%